The relationship of maternal and child methylation of the glucocorticoid receptor NR3C1 during early childhood and subsequent child psychopathology at school-age in the context of maternal interpersonal violence-related post-traumatic stress disorder - Cordero, María I.; Stenz, Ludwig; Moser, Dominik A.; Rusconi Serpa, Sandra; Paoloni-Giacobino, Ariane; Schechter, Daniel Scott (Frontiers in Psychiatry, 2022)
Introduction: Interpersonal violent (IPV) experiences when they begin in childhood and continue in various forms during adulthood often lead to chronic post-traumatic stress disorder (PTSD) that is associated in multiple studies with hypocortisolism and lower percentage of methylation of the promoter region of the gene coding for the glucocorticoid receptor (NR3c1). This prospective, longitudinal study examined the relationship of NR3c1 methylation among mothers with IPV-related PTSD and their toddlers and then looked at the relationship of maternal NR3c1 methylation and child psychopathology at school age. Methods: Forty-eight mothers were evaluated for life-events history and post-traumatic stress disorder via structured clinical interview when their children were ages 12-42 months (mean age 26.7 months, SD 8.8). Their children’s psychopathology in terms of internalizing symptoms and externalizing behaviors was evaluated using the Child Behavior Checklist at ages 5-9 years (mean age 7 years, SD 1.1). Percentage of methylation for the NR3C1 gene promoter region was assessed from DNA extracted from maternal and child saliva using bisulfite pyrosequencing. Data analysis involved parametric and non-parametric correlations and multiple linear and logistic regression modelling. Results: Logistic regression models using child NR3C1 methylation as the dependent variable and maternal NR3C1 methylation and PTSD group status as predictors, as well as the interaction indicated that all three of these significantly predicted child NR3C1 methylation. These findings remained significant when controlling for child age, sex and maternal child abuse history. Overall, maternal NR3C1 methylation when children were toddlers was negatively and significantly associated with child externalizing behaviour severity at school age. Discussion: We found that correlations between mothers and their children of NR3C1 methylation levels overall and at all individual CpG sites of interest were significant only in the IPV-PTSD group. The latter findings support that NR3C1 methylation in mothers positively and statistically significantly correlates with NR3C1 methylation in their children only in presence of IPV-PTSD in the mothers. This maternal epigenetic signature with respect to this glucocorticoid receptor is significantly associated with child behaviour that may well pose a risk for intergenerational transmission of violence and related psychopathology.